Coupling effect between electromigration and joule heating on the failure of ball grid array in 3D integrated circuit technology - Yifan Yao; Yuxuan An; K.N. Tu; Yingxia Liu (Journal of Materials Research and Technology, 2024)
Ball Grid Array (BGA) packaging method has been widely used in microelectronic devices, and electromigration (EM) in BGA is a crucial reliability issue, determining the performance of the products. Herein, we report a new failure mode induced by a coupling effect of EM and Joule heating in BGA structure. The test sample consists of a roll of 500 μm-BGA solder joints with upper and lower Cu under-bump-metallization (UBM) of different thicknesses, 16 μm, and 68 μm, respectively. Open failures of the thinner cathodic Cu UBM at the contacting area with solder joint were observed under four different EM conditions (130 °C-3000 A/cm2, 160 °C-2300 A/cm2, 160 °C-3000 A/cm2, and 160 °C-4600 A/cm2). Infrared (IR) results reveal the temperature at the thinner Cu UBM is higher than that in the solder joint as well as at the thicker Cu UBM. Simulation results elucidate the current density at the contacting area is about 22 times higher than the average density in the solder joint, so the effect of current crowding can be very serious in the failure site. Furthermore, severe current crowding and Joule heating promote the nucleation rate of voids at the joint location, which can further increase the current density and temperature, leading to a positive feedback effect until an open failure occurs in the circuitry. Our analysis enables the discussion of a coupling failure mode of EM and Joule heating in BGA, and provides a valuable guide of device design against EM failure in consumer electronic products.